2016
DOI: 10.3168/jds.2015-10564
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of different cheeses: Affecting factors and prediction by near infrared spectroscopy

Abstract: In this study, we analyzed antioxidant capacity of 224 cheese samples prepared using 16 varied mixtures of milk from cows, ewes, and goats, in 2 manufacturing seasons (winter and summer), and over 6mo of ripening. Antioxidant capacity was evaluated using the spectrophotometric 2,2-azinobis(3-ethylenebenzothiazoline-6-sulfonic acid) (ABTS) method. Total antioxidant capacity was significantly correlated with season of manufacturing and time of ripening but not with animal species providing the milk. Moreover, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
0
35
0
2
Order By: Relevance
“…; Usta and Yilmaz‐Ersan ; Roy and Deepak ; Revilla et al . ). The total antioxidant capacity of kefir refers to the antioxidant power of biochemical components measuring the antioxidant response to counter the free radicals produced.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Usta and Yilmaz‐Ersan ; Roy and Deepak ; Revilla et al . ). The total antioxidant capacity of kefir refers to the antioxidant power of biochemical components measuring the antioxidant response to counter the free radicals produced.…”
Section: Discussionmentioning
confidence: 97%
“…), (ii) uric acid reduces ferric ion activity, (iii) lactic acid bacteria found in milk demonstrate iron-scavenging/reducing activity and the scavenging of reactive oxygen species (OH . , H 2 O 2 ), (iv) lactoferrin has the activity of chelating metal, (v) sulfhydryl groups formed as a result of heat treatment act as free radical scavengers, (vi) beta-carotene and retinol Revilla et al 2016). The total antioxidant capacity of kefir refers to the antioxidant power of biochemical components measuring the antioxidant response to counter the free radicals produced.…”
Section: Discussionmentioning
confidence: 99%
“…Faccia et al (2015) reported satisfactory production of Fior di latte cheeses from sheep and goat milk after methodological modifications from the standard cow Fior di latte process. Providing additional support to the findings, Revilla et al (2016) analyzed the antioxidant capacity of 224 cheese samples in Spain, prepared using mixtures of milk from cows, sheep, and goats, in 2 manufacturing seasons (winter and summer) and over 6 month of ripening. Although animal species was not a significant factor correlated with total antioxidant capacity, statistically significant correlations were found between total antioxidant capacity and season of manufacturing (higher antioxidant activity in summer cheeses), time of ripening, retinol, fat and protein percentages, and some minerals (K, Mg, Na, and P;Revilla et al 2016).…”
Section: International Advanced Research On Designed Fermented Goat Mmentioning
confidence: 96%
“…Providing additional support to the findings, Revilla et al (2016) analyzed the antioxidant capacity of 224 cheese samples in Spain, prepared using mixtures of milk from cows, sheep, and goats, in 2 manufacturing seasons (winter and summer) and over 6 month of ripening. Although animal species was not a significant factor correlated with total antioxidant capacity, statistically significant correlations were found between total antioxidant capacity and season of manufacturing (higher antioxidant activity in summer cheeses), time of ripening, retinol, fat and protein percentages, and some minerals (K, Mg, Na, and P;Revilla et al 2016). Recently, many studies revealed adequate viability of probiotics in goat's milk products throughout storage period as shown in Table 1.…”
Section: International Advanced Research On Designed Fermented Goat Mmentioning
confidence: 96%
“…Among these traits, minerals, fatty acids, cholesterol, volatile compounds and sensory properties stand out [10]. For example, some authors evaluated the potential of NIRS to predict the total antioxidant capacity of different cheeses, ending up with positive conclusions and perspectives [36]. Moreover, R 2 EV of 0.50 for cholesterol content has been reported [37]; as regards major minerals, the same authors found R 2 EV from 0.65 (potassium) to 0.94 (phosphorus).…”
Section: Application Of Infrared Spectroscopy In Milkmentioning
confidence: 99%